(untitled) (Fiep Bulletin - online, 2013)
In each time, the society values a body type. It is an emblem where the culture inserts their signs and/or coats of arms. It is noticed, in the modernity, the relevance of a deep study on the women’s fight for their ideals for us understand how it happens the appropriation of the feminine body in the sport. The objective of this work was to investigate if is masculinization of the feminine body in the sporting way. It opted for a research of the qualitative type, accomplished under the form of case study, being adopted the deepened study of theoretical referential and transcriptions of interviews. A woman interviewed was with 29 years, body building former-apprentice. In agreement with her speech in the interviews, it was evident the influence of the communication means in the popularization of the body idealized by a lot of women, what frequently contributes so that the search for a body considered perfect increases. It was evident in many speeches that the women treat their bodies today, in a way almost that irrational. It is inferred, starting from this case study, that it very still needs to be researched and illustrious. There is really a tendency to the masculinization of this body and, this can happen through the incessant search for the ideal body and for the great influence of the media.